To solve the compound inequality \(-2 \leq 2x + 13 - 4 < 1\), we can break it into two parts and solve for \(x\).
-
Start with the left part of the inequality: \[ -2 \leq 2x + 13 - 4 \] Simplifying gives: \[ -2 \leq 2x + 9 \] Subtracting 9 from both sides: \[ -11 \leq 2x \] Dividing by 2: \[ -\frac{11}{2} \leq x \quad \text{or} \quad x \geq -\frac{11}{2} \]
-
Now, solve the right part of the inequality: \[ 2x + 13 - 4 < 1 \] Simplifying gives: \[ 2x + 9 < 1 \] Subtracting 9 from both sides: \[ 2x < -8 \] Dividing by 2: \[ x < -4 \]
Now we have: \[ -\frac{11}{2} \leq x < -4 \]
Since \(-\frac{11}{2} = -5.5\), we can express the solution as: \[ -\frac{11}{2} \leq x < -4 \]
Now let's find the corresponding option in the responses:
- \( { x : -\frac{3}{2} \leq x < 1 } \) is not correct.
- \( { x : 3 \leq x < 7 } \) is not correct.
- \( { x : -\frac{11}{2} \leq x < -4 } \) is correct but given incorrectly in the response form.
- \( { x : -\frac{5}{2} \leq x < 7 } \) does not match.
In conclusion, none of the provided options seem to express the correct solution. The correct answer, based on the solved inequalities, is: \[ { x : -\frac{11}{2} \leq x < -4 } \]
Since it's not one of the answers, please double-check the options you provided.